Creating the Organizational 'Atmosphere' for Improved Communication - Tousignant, Fabienne (Relations industrielles / Industrial Relations, 1954)
The article reviews "Creating the Organizational 'Atmosphere' for Improved Communication," by Harry D. Kolb, article in ''Personnel", published by the American Management Association, May 1954, pp. 482-487.